(untitled) (Palimpsesto, 2017)
The expense accounts for the wine production in Villavicencio, in southern Maule, are the basis for an analysis of the different elements present in its production: workers and their maintenance, supplies and tools, and the production process. The information comes from the years 1711-1726, which allows us to start to understand the processes that were carried out, and what was required of each participant at each stage. By this we hope to begin to understand "micro-spaces" such as this hacienda in their own dimension, within the world of wine production, by studying the products required for its work, and the essential human component.